TANTANGAN PENGEMBANGAN IPTEK TERHADAP PANCASILA DALAM KEMAHASISWAAN - Febi Aisqil Jamilah; Nila Amalia Nabila; Nurdiana Nurdiana; Susiba Susiba (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This abstract discusses the impact of the development of science and technology (DST) on students as the nation’s next generation. The main challenge is to integrate science and technology with Pancasila values ​​as a moral foundation. This research analyzes challenges such as individualism, dependence on technology, and the decline in the value of mutual cooperation and nationalism. The proposed solutions include the integration of Pancasila in academic activities, development of a digital ethics curriculum, and increasing social awareness through student organizations. It is hoped that the results of this study can help students face changes in science and technology wisely, in accordance with the nation’s vision based on Pancasila.